Diskriminasi Gender dalam Pendidikan dan Tempat Kerja : Analisis Faktor Sosial dan Agama - Aceng Murtado; Ade Fakih Kurniawan; Suadi Sa’ad (Journal on Education, 2024)
Women are a problem who are often victims of discrimination in almost all levels of Indonesian society and even throughout the world. It is very clear that the compromise is for society to let go of the patriarchal culture that has existed for thousands of years and requires women to be under the control of men. Discrimination is actions and practices that treat certain people or groups differently and unfairly. Meanwhile, gender is a characteristic inherent in men and women which is constructed socially and culturally. So gender discrimination in the short term means unfair actions towards men and women. Meanwhile, this research uses qualitative research methods, with phenomenology as the type of research. The results of this research are that women are hindered by many societal empowerments, including discrimination, exploitation, marginalization, subordination, stereotypes, and negative labeling of women. In this paper there are 2 study analyzes: First, social factor analysis, there are at least 6 social factors that cause gender disparities: social and cultural norms, education, family roles, gender violence, legal policies and finally the strong patriarchal culture. Second, analysis of religious factors, from this religious factor the author includes 3 key problems that also cause gender disparities: Tafsir of the Koran, Islamic law (Shari'ah) and teachings of ulama. The impact of this inequality has implications for important problems experienced by women, starting from lack of access to education, career choices, and unequal distribution of roles in the household.